Resiliensi Budaya Mahasiswa Dan Implikasinya Terhadap Pedagogi Kedamaian - Sari, Syska Purnama; Aryansah, Januar Eko; Ahman, Ahman; Saripah, Ipah (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2023)
Resilience can be developed from cultural support, so the uniqueness and the whole cultural construct are important to take into account. The ability of individuals to be able to adapt from the pressures experienced in their lives through the cultural values ​​of the surrounding environment is a personal competence that must be developed by educators. Cultural resilience can be developed through the pedagogy of peace. The purpose of this article is to describe the cultural resilience of PGRI Palembang University students and their implications for peace pedagogy. The research method is descriptive quantitative with 80 students in semester II, IV and VI 2021. The measurement of cultural resilience is based on the theory of Reivich and Shatte and ClaussEhlers, aspects of cultural resilience consist of emotion regulation, emotional control, impulse control, reaching out, adaptive coping, global coping and socio-cultural support. The results is the cultural resilience of PGRI Palembang University students was in the medium category. With the achievement of the highest aspect is emotional regulation, and the lowest is socio-cultural support. Efforts to develop cultural resilience are through guidance and peace counseling using cultural strategies.